A low-cost alkaline secondary battery positive electrode material and its preparation method and application

By introducing layered hydroxide into the MnO2 positive electrode material of zinc-manganese secondary battery to form a composite positive electrode material, the problems of low material conductivity and poor structural stability are solved, and the capacity, platform and cycle stability performance of the battery are significantly improved.

CN115312732BActive Publication Date: 2025-05-02XINXIANG CHAOLI NEW ENERGY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211049383.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2025-05-02
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

The MnO2 positive electrode material of zinc-manganese alkaline secondary battery has problems such as low conductivity and poor structural stability, resulting in poor capacity performance, rate performance and cycle stability, limiting the widespread application of zinc-manganese secondary batteries.

Method used

A composite positive electrode material composed of manganese dioxide and layered hydroxide [NixMyAZ(OH)2]·[(Ba-)b·mH2O] or its variants is used to form a three-dimensional structure, a multi-stage pore structure or a cladding structure through high-energy ball milling treatment to improve the structural stability and electrochemical properties of the material.

Benefits of technology

The discharge capacity, discharge platform and cycle stability of the composite positive electrode material are improved, making it suitable for the application of zinc-manganese secondary batteries, significantly improving the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115312732B_ABST
    Figure CN115312732B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-cost alkaline secondary battery positive electrode material and a preparation method and application thereof, belonging to the technical field of alkaline secondary batteries. The technical scheme of the present invention mainly includes: a low-cost alkaline secondary positive electrode active material, or a composite positive electrode material composed of manganese dioxide and a partially oxidized layered hydroxide, or a composite positive electrode material composed of manganese dioxide and a layered oxyhydroxide, or a composite positive electrode material composed of manganese dioxide, a conductive material and a layered hydroxide or a partially oxidized layered hydroxide or a layered oxyhydroxide. The present invention also specifically discloses a preparation method of the zinc negative electrode material for the alkaline secondary battery and a zinc-nickel secondary battery using the negative electrode material. Compared with the traditional manganese electrode, the composite positive electrode material prepared by the present invention has the advantages of high discharge platform, high gram capacity, good cycle stability, etc., which significantly improves the cycle stability and reversibility of the zinc-manganese alkaline secondary battery and improves its cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alkaline secondary battery positive electrode materials, and in particular relates to a low-cost alkaline secondary battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Compared with other batteries, zinc-manganese alkaline secondary batteries have the advantages of low cost, environmental protection, non-toxicity, and good safety. They have broad application prospects in the fields of energy storage and civilian markets. MnO2 is a metal oxide, a semiconductor material, and a common positive electrode material for primary dry batteries. In zinc-manganese alkaline secondary batteries, the MnO2 positive electrode has low conductivity (conductivity is 10 -5 ~10 -6 S cm -1 ), poor structural stability and other issues, which seriously restrict the widespread application of zinc-manganese alkaline secondary batteries. MnO2 has a large volume expansion and contraction during the charge and discharge process, and is prone to generate electrochemically inert low-valent manganese oxides, such as Mn3O4, which causes the structure of the positive electrode material to be destroyed and the amount of active substances to be reduced, thus affecting the electrochemical performance of the battery. Therefore, the capacity performance, rate performance and cycle stability of zinc-manganese alkaline secondary batteries are still difficult to meet the needs of actual applications.

[0003] Zinc-manganese secondary batteries are mainly composed of several main parts such as positive electrode, separator, electrolyte, negative electrode, etc. The research on the positive electrode focuses on the development of new positive electrode materials and the modification of manganese dioxide materials. The modified MnO2 obtained by physical doping, chemical doping and electrochemical deposition doping has greatly improved its rechargeability. Moreover, the reversibility of various crystal forms of MnO2 has also been improved to a certain extent after modification. However, the rechargeable zinc-manganese secondary battery is still limited by its poor cycle stability in practical applications. Therefore, the development of new positive electrode materials is still the key to the technological progress of the zinc-manganese secondary battery. Summary of the invention

[0004] The present invention overcomes the shortcomings of the current zinc-manganese alkaline secondary battery MnO2 positive electrode material and provides a low-cost alkaline secondary battery positive electrode material and a preparation method thereof. The positive electrode material prepared by the method has higher discharge capacity, higher discharge platform and better cycle stability, and can be used to prepare the zinc-manganese secondary battery positive electrode.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a low-cost alkaline secondary battery positive electrode material, characterized in that: the positive electrode material is composed of manganese dioxide and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b·mH2O] composite cathode material, or manganese dioxide and partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] composite cathode material, or manganese dioxide and layered oxyhydroxide [Ni x M y A Z OOH] composite positive electrode material, or manganese dioxide, conductive material and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or layered oxyhydroxide [Ni x M y A Z OOH] to form a composite positive electrode material, the composite positive electrode material has a three-dimensional structure, a multi-level pore structure or a coating structure, or a mixed structure of multiple structures, wherein M is Bi or Ti, A is one or two of Ce, Al, Zn, Ca, Mg, Co, Y, Ga, Sb, Yb or Cu, and B a- OH − , Cl - 、F - PO4 3- 、SO4 2- 、CO3 2− 、NO3 − , BO2 - 、MoO4 2- or WO4 2- One or more of, 0.9≥x≥0.5, 0.3≥y≥0.1, 0.2≥z≥0.01, x+y+z=1, b>0, m>0.

[0006] It is further defined that the layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(Ba- ) b ·mH2O] or layered oxyhydroxide [Ni x M y A Z The mass percentage of OOH] is 5%-75%; preferably 10%-40%.

[0007] It is further defined that the conductive material is one or two of graphene, carbon nanotubes, acetylene black, flake graphite, cobalt oxyhydroxide, nitrogen carbide, titanium carbide, niobium carbide or titanium nitride, and the mass percentage of the conductive material in the composite positive electrode material is 0.5%-20%; the manganese dioxide is one or more of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2 or ε-MnO2, preferably γ-MnO2.

[0008] A method for preparing a low-cost alkaline secondary battery positive electrode material, characterized in that the manganese dioxide and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b The specific preparation process of the composite positive electrode material composed of ·mH2O] is as follows:

[0009] Step S1, ball-milling a manganese dioxide precursor, and sieving to obtain a manganese dioxide precursor for standby use;

[0010] Step S2, dissolving a soluble nickel salt, a soluble bismuth salt or a soluble titanium salt, and a metal salt of A in deionized water to prepare a composite salt solution, dissolving an alkaline hydroxide in deionized water to prepare an alkaline solution, adding the alkaline solution to the composite salt solution at 15-50° C., and continuously stirring until the pH of the suspension reaches 7-11 after the reaction is completed, reacting the obtained suspension at 50-95° C. for 5-48 hours, cooling to room temperature, filtering, washing, and drying to obtain a powder, transferring the obtained powder to a solution prepared by one or more of an alkaline hydroxide, a phosphate, a tungstate, a molybdate, a chloride, a fluoride, a carbonate, a metaborate, or a borate, treating at 25-200° C. for 1-24 hours under an inert atmosphere or air conditions, filtering, washing, and drying to obtain a layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O];

[0011] Step S3, mixing the manganese dioxide precursor obtained in step S1 and the layered hydroxide [Ni x M y A Z(OH)2]·[(B a- ) b ·mH2O] and then subjected to high-energy ball milling to obtain a composite positive electrode material.

[0012] A method for preparing a low-cost alkaline secondary battery positive electrode material, characterized in that the manganese dioxide and the partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] composite positive electrode material and manganese dioxide and layered oxyhydroxide [Ni x M y A Z The specific preparation process of the composite positive electrode material composed of OOH is as follows:

[0013] Step S1, ball-milling a manganese dioxide precursor, and sieving to obtain a manganese dioxide precursor for standby use;

[0014] Step S2, dissolving a soluble nickel salt, a soluble bismuth salt or a soluble titanium salt, and a metal salt of A in deionized water to prepare a composite salt solution, dissolving an alkaline hydroxide in deionized water to prepare an alkaline solution, adding the alkaline solution to the composite salt solution at 15-50° C., and continuously stirring until the pH of the suspension reaches 7-11 after the reaction is completed, reacting the obtained suspension at 50-95° C. for 5-48 hours, cooling to room temperature, filtering, washing, and drying to obtain a powder, transferring the obtained powder to a solution prepared by one or more of an alkaline hydroxide, a phosphate, a tungstate, a molybdate, a chloride, a fluoride, a carbonate, a metaborate, or a borate, treating the solution at 25-200° C. for 1-24 hours under an inert atmosphere or air, filtering, washing, and drying to obtain a layered hydroxide, and oxidizing the layered hydroxide by a chemical oxidation or electrolytic oxidation method to obtain a partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH];

[0015] Step S3, the manganese dioxide precursor obtained in step S1 and the partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH] and then subjected to high-energy ball milling to obtain a composite positive electrode material.

[0016] A method for preparing a low-cost alkaline secondary battery positive electrode material, characterized in that the manganese dioxide, conductive material and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or layered oxyhydroxide [Ni x M y A Z The specific preparation process of the composite positive electrode material composed of OOH is as follows:

[0017] Step S1, ball-milling a manganese dioxide precursor, and sieving to obtain a manganese dioxide precursor for standby use;

[0018] Step S2, dissolving a soluble nickel salt, a soluble bismuth salt or a soluble titanium salt, and a metal salt of A in deionized water to prepare a composite salt solution, dissolving an alkaline hydroxide in deionized water to prepare an alkaline solution, adding the alkaline solution to the composite salt solution at 15-50° C., and continuously stirring until the pH of the suspension reaches 7-11 after the reaction is completed, reacting the obtained suspension at 50-95° C. for 5-48 hours, cooling to room temperature, filtering, washing, and drying to obtain a powder, transferring the obtained powder to a solution prepared by one or more of an alkaline hydroxide, a phosphate, a tungstate, a molybdate, a chloride, a fluoride, a carbonate, a metaborate, or a borate, treating at 25-200° C. for 1-24 hours under an inert atmosphere or air conditions, filtering, washing, and drying to obtain a layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O], the layered hydroxide is oxidized by chemical oxidation or electrolytic oxidation to obtain a partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Nix M y A Z OOH];

[0019] Step S3, mixing the manganese dioxide precursor obtained in step S1, the conductive material and the layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH] is uniformly dispersed in water or an organic solvent, reacted in a normal pressure container at 15-90° C., and then the product is dried to obtain a composite positive electrode material.

[0020] It is further defined that the soluble nickel salt is one or more of nickel nitrate, nickel sulfate, nickel acetate or nickel chloride; the soluble bismuth salt is bismuth nitrate; the soluble titanium salt is titanium sulfate; the A metal salt is one or more of cerium nitrate, cerium chloride, aluminum nitrate, aluminum chloride, aluminum sulfate, zinc nitrate, zinc sulfate, zinc chloride, calcium acetate, calcium chloride, magnesium acetate, magnesium chloride, cobalt nitrate, cobalt chloride, cobalt sulfate, yttrium nitrate, yttrium sulfate, yttrium chloride, gallium nitrate, antimony sulfate, antimony chloride, ytterbium nitrate, ytterbium chloride, copper chloride, copper sulfate or copper nitrate; the phosphate is one of potassium phosphate, sodium hydrogen phosphate or sodium phosphate or more; the tungstate is one or more of potassium tungstate, sodium tungstate or lithium tungstate; the molybdate is one or more of potassium molybdate or sodium molybdate; the chloride is one or more of potassium chloride or sodium chloride; the fluoride is one or more of potassium fluoride or sodium fluoride; the carbonate is one or more of potassium carbonate or sodium carbonate; the metaborate is one or more of potassium metaborate, sodium metaborate or lithium metaborate; the borate is one or more of potassium metaborate, sodium metaborate or lithium metaborate; the alkaline hydroxide is one or more of sodium hydroxide, potassium hydroxide or lithium hydroxide.

[0021] An alkaline secondary battery positive electrode plate, characterized in that the alkaline secondary battery positive electrode plate is made from the above-mentioned low-cost alkaline secondary battery positive electrode material.

[0022] It is further defined that the low-cost alkaline secondary battery positive electrode material contains an additive with a mass fraction of 0.5% to 10%, and the additive is one or two of chromium oxide, chromium hydroxide, strontium oxide, strontium hydroxide, ytterbium oxide or antimony-doped tin oxide.

[0023] An alkaline secondary battery comprises a battery housing, a plate group sealed in the battery housing and an electrolyte, wherein the plate group comprises a positive plate, a negative plate and a diaphragm, and is characterized in that the positive plate adopts the alkaline secondary battery positive plate, and the electrolyte adopts a potassium hydroxide alkaline solution to which sodium hexafluoroantimonate with a mass fraction of 0.1% to 2% is added.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: the positive electrode material of the alkaline secondary battery of the present invention is composed of manganese dioxide and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] to form a composite negative electrode material, which has a three-dimensional structure. First, Bi or Ti is filled in the tunnel and interlayer during the charge and discharge process of MnO2, so that protons and electrons can flow freely between the lattices, inhibiting the expansion of the lattice and stabilizing the lattice and active sites. Secondly, by introducing other elements into the layered hydroxide, the binding force between the metal and the oxygen layer can be enhanced, and the structural stability and cycle reversibility of the composite positive electrode material during the charge and discharge process can be effectively improved. Electrochemical tests have shown that compared with uncomposite positive electrode materials, the composite positive electrode material prepared by the present invention has higher discharge capacity, higher discharge platform and better cycle stability as an alkaline secondary battery positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of the composite positive electrode material prepared in Example 1;

[0026] Figure 2 is an element distribution diagram of the composite positive electrode material prepared in Example 1;

[0027] Figure 3 is the XRD pattern of the composite positive electrode material prepared in Example 1;

[0028] Figure 4 is the discharge curve of the composite cathode material and MnO2 prepared in Example 1;

[0029] Figure 5 is a scanning electron microscope image of the composite positive electrode material prepared in Example 13;

[0030] Figure 6 is the XRD pattern of the composite positive electrode materials prepared in Examples 13 and 14;

[0031] Figure 7 This is a discharge curve diagram of the composite positive electrode material and MnO2 prepared in Example 13. DETAILED DESCRIPTION

[0032] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0033] Example 1

[0034] MnO2 / [Ni 0.8 Bi 0.1 Al 0.1 (OH)2·[(A a- ) b ·mH2O]( A=Cl - , b=0.1, m=2) Preparation of composite positive electrode materials:

[0035] First, nickel nitrate, bismuth nitrate and aluminum chloride were mixed in a molar ratio of Ni / Bi / Al=0.8 / 0.1 / 0.1 in a fume hood and prepared into a composite salt solution with a molar concentration of 0.5 mol / L at 25°C; potassium hydroxide was dissolved in deionized water to prepare an alkaline solution with a molar concentration of 3 mol / L; the alkaline solution was added dropwise to the mixed salt solution at 25°C using a peristaltic pump, and stirred continuously until the pH of the reaction suspension reached 7.5. After the reaction was completed, the obtained suspension was reacted at 80°C for 20 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder was transferred to a sodium chloride solution with a molar concentration of 0.5 mol / L, treated at 150°C for 12 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide.

[0036] Then, the manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor for use. The manganese dioxide precursor and the layered hydroxide prepared above are mixed at a mass ratio of 3:1 and then subjected to high-energy ball milling to obtain a manganese dioxide composite nickel-bismuth multi-layered hydroxide composite positive electrode material. The scanning electron microscope, element distribution, XRD spectrum and charge-discharge curve of the sample are shown in FIG. Figure 1-5 shown.

[0037] Example 2

[0038] MnO2 / partially oxidized layered hydroxide [Ni 0.7 Bi 0.2 Cu 0.1 (OH)2·[(A a- ) b ·mH2O](A=WO42- OH - , n=0.2, m=2) Preparation of composite positive electrode materials:

[0039] First, nickel chloride, bismuth nitrate and cupric chloride were mixed in a molar ratio of Ni / Bi / Cu=0.7 / 0.2 / 0.1 in a fume hood to prepare a composite salt solution with a molar concentration of 0.4 mol / L at room temperature; sodium hydroxide was dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2 mol / L; at room temperature, the alkaline solution was added dropwise to the mixed salt solution, and the mixture was stirred continuously until the pH of the reaction suspension reached 9. After the reaction is completed, the obtained suspension is reacted at 90°C for 10 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to an alkaline solution of sodium tungstate with a molar concentration of 0.5 mol / L, and treated at 120°C for 15 hours under the protection of inert gas nitrogen, filtered, washed, and a layered hydroxide sample is obtained, and then 5g of the layered hydroxide sample is added to 100mL of a solution containing 5g of potassium persulfate and 2M potassium hydroxide under the protection of nitrogen, stirred for 20 minutes, filtered, washed, and vacuum dried at 80°C for 5 hours to obtain a partially oxidized layered hydroxide.

[0040] Then, the manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor for use. The manganese dioxide precursor and the partially oxidized layered hydroxide prepared above are mixed at a mass ratio of 2:1 and then subjected to high-energy ball milling to obtain a MnO2 / partially oxidized layered hydroxide composite positive electrode material.

[0041] Example 3

[0042] MnO2 / Layered oxyhydroxide[Ni 0.6 Bi 0.2 Sb 0.2 OOH·[(A a- ) b ·mH2O](A=MoO4 2- OH - , b=0.2, m=2) Preparation of composite positive electrode materials:

[0043] First, nickel sulfate, bismuth nitrate and antimony chloride were mixed in a molar ratio of Ni / Bi / Sb=0.6 / 0.2 / 0.2 in a fume hood and then prepared into a composite salt solution with a molar concentration of 1.0 mol / L at room temperature; sodium hydroxide was dissolved in deionized water to prepare an alkaline solution with a molar concentration of 1 mol / L; at room temperature, the alkaline solution was added dropwise to the mixed salt solution, and the mixture was stirred continuously until the pH of the reaction suspension reached 8.5. After the reaction is completed, the obtained suspension is reacted at 60°C for 24 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to an alkaline solution of sodium molybdate with a molar concentration of 3 mol / L, and treated at 180°C for 4 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide, and then under the protection of nitrogen, 5 g of the layered hydroxide is added to 100 mL of a solution containing 15 g of potassium persulfate and 4 M potassium hydroxide, stirred for 60 minutes, filtered, washed, and vacuum dried at 80°C for 5 hours to obtain a layered hydroxy oxide.

[0044] Then, the manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor for use. The manganese dioxide precursor and the layered oxyhydroxide prepared above are mixed at a mass ratio of 4:1 and then subjected to high-energy ball milling to obtain a MnO2 / layered oxyhydroxide composite positive electrode material.

[0045] Example 4

[0046] MnO2 / layered hydroxide [Ni 0.8 Bi 0.1 Ce 0.05 Zn 0.05 (OH)2·[(A a- ) b ·mH2O]( A=F - PO4 3- , BO2 − , n=0.2, m=2) Preparation of composite positive electrode materials:

[0047] First, nickel acetate, bismuth nitrate, cerium nitrate and zinc chloride were mixed in a molar ratio of Ni / Bi / Ce / Zn=0.8 / 0.1 / 0.05 / 0.05 in a fume hood and then prepared into a composite salt solution with a molar concentration of 2.0 mol / L at room temperature; potassium hydroxide was dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2 mol / L; at room temperature, the alkaline solution was added dropwise to the mixed salt solution, and the reaction suspension was stirred continuously until the pH of the reaction suspension reached 9. After the reaction was completed, the obtained suspension was reacted at 80°C for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder was transferred to a mixed solution of sodium fluoride, sodium phosphate and sodium metaborate with a molar concentration of 3.0 mol / L (the molar ratio of sodium fluoride, sodium phosphate and sodium metaborate was 0.2:0.2:1), and treated at 150°C for 12 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide.

[0048] Then, the manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor for use. The manganese dioxide precursor and the prepared layered hydroxide are mixed at a mass ratio of 5:2 and then subjected to high-energy ball milling to obtain a manganese dioxide composite nickel-bismuth multi-layered hydroxide composite positive electrode material.

[0049] Example 5

[0050] MnO2 / layered hydroxide [Ni 0.8 Bi 0.1 Al 0.05 Y 0.05 (OH)2·[(A a- ) n ·mH2O](A=Cl - , n=0.2, m=2) / Preparation of graphene composite materials:

[0051] First, the manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor for standby use. Then, nickel nitrate, bismuth nitrate, aluminum chloride and yttrium nitrate are mixed in a molar ratio of Ni / Bi / Al / Y=0.8 / 0.1 / 0.05 / 0.05 in a fume hood and prepared into a composite salt solution with a molar concentration of 0.5 mol / L at 25°C; potassium hydroxide solid is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 3 mol / L; the alkaline solution is added dropwise to the mixed salt solution at 25°C using a peristaltic pump, and stirred continuously until the pH of the reaction suspension reaches 8. After the reaction is completed, the obtained suspension is reacted at 80°C for 12h, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to a sodium chloride solution with a molar concentration of 0.5 mol / L, treated at 150°C for 12h under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide. The manganese dioxide precursor, graphene, and the layered hydroxide prepared above are ultrasonically dispersed into an aqueous solution at a mass ratio of 4:1:1, and then freeze-dried to obtain a MnO2 / layered hydroxide / graphene composite positive electrode material.

[0052] Example 6

[0053] MnO2 / Layered oxyhydroxide[Ni 0.6 Bi 0.2 Sb 0.2 OOH·[(A a- ) n ·mH2O]( A=MoO4 2- OH - , n=0.2, m=2) / acetylene black composite positive electrode material preparation:

[0054] The manganese dioxide solid powder is ground and sieved to obtain a manganese dioxide precursor for use. The manganese dioxide precursor, acetylene black, and the layered oxyhydroxide prepared in Example 3 are subjected to high-energy ball milling at a mass ratio of 5:2:3 to obtain a MnO2 / layered oxyhydroxide / acetylene black composite positive electrode material.

[0055] Example 7

[0056] MnO2 / layered hydroxide [Ni 0.8 Bi 0.1 Ce 0.05 Zn 0.05 (OH)2·[(A a- ) n ·mH2O](A=F - PO4 3- , BO2 − , n=0.2, m=2) / Preparation of carbon nanotube composite positive electrode materials:

[0057] First, the manganese dioxide solid powder is ground and sieved to obtain a manganese dioxide precursor for use. Then, the manganese dioxide precursor, carbon nanotubes and the layered hydroxide prepared in Example 4 are subjected to high-energy ball milling at a mass ratio of 6:1:2 to obtain a MnO2 / layered hydroxide / carbon nanotube composite positive electrode material.

[0058] Example 8

[0059] MnO2 / layered hydroxide [Ni 0.8 Bi 0.1 Ce 0.06 Y 0.04 (OH)2·(A a- ) n ·mH2O] (A=Cl - , n=0.2, m=2) / Preparation of flake graphite composite positive electrode material:

[0060] First, nickel acetate, bismuth nitrate, cerium nitrate and yttrium sulfate were mixed in a fume hood at a molar ratio of Ni / Bi / Ce / Y=0.8 / 0.1 / 0.06 / 0.04 to prepare a composite salt solution with a molar concentration of 2.0 mol / L at room temperature; flake graphite was weighed and ultrasonically dispersed into the composite salt solution, wherein the flake graphite and the target prepared layered hydroxide [Ni 0.8 Bi 0.1 Ce 0.06 Y 0.04 (OH)2 ·(A a- ) n ·mH2O] is controlled to have a mass ratio of 1:3. Potassium hydroxide is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2 mol / L; at room temperature, the alkaline solution is added dropwise to the mixed salt solution, and stirred continuously until the pH of the reaction suspension reaches 9. After the reaction is completed, the obtained suspension is reacted at 80°C for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to a mixed solution of sodium chloride with a molar concentration of 1.0 mol / L, treated at 100°C for 4 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide / flake graphite composite material.

[0061] The manganese dioxide solid powder is ground and sieved to obtain a manganese dioxide precursor for use. The manganese dioxide precursor and the prepared layered hydroxide / flake graphite composite material are subjected to high-energy ball milling at a mass ratio of 3:4 to obtain a MnO2 / layered hydroxide / flake graphite composite positive electrode material.

[0062] Preparation of positive electrode plates based on the composite positive electrode materials obtained in Examples 1-8: 0.4 g of the composite positive electrode materials prepared in each example and 0.1 g of superconducting carbon black were ground in an agate mortar for 20 min and mixed evenly. Then, 0.05 g of a CMC solution with a mass concentration of 2.5% and 0.05 g of a PTFE aqueous solution with a mass concentration of 60% were added and mixed evenly to prepare positive electrode slurry, which was coated on the nickel foam through a slurry drawing mold, and after vacuum drying at 60° C. for 12 h, the positive electrode plates were prepared by pressing at a pressure of 12 MPa for 10 s.

[0063] Example 9

[0064] Preparation of 5wt% Cr(OH)3 doped positive plate:

[0065] 0.375 g of the composite positive electrode material prepared in Example 1, 0.025 g of chromium hydroxide and 0.1 g of superconducting carbon black were ground in an agate mortar for 20 min and mixed evenly. Then 0.05 g of a CMC solution with a mass concentration of 2.5% and 0.05 g of a PTFE aqueous solution with a mass concentration of 60% were added and mixed evenly to prepare a positive electrode slurry, which was coated on the nickel foam through a slurry drawing mold, and after vacuum drying at 60° C. for 12 h, it was pressed for 10 s at a pressure of 12 MPa to prepare a positive electrode plate.

[0066] Example 10

[0067] Preparation of positive electrode plate doped with 1wt% Sr(OH)2 and 2wt% Cr2O3:

[0068] 0.385g of the composite positive electrode material prepared in Example 2, 0.005g of strontium hydroxide, 0.01g of chromium oxide and 0.1g of superconducting carbon black were ground in an agate mortar for 20 minutes and mixed evenly. Then, 0.05g of a CMC solution with a mass concentration of 2.5% and 0.05g of a PTFE aqueous solution with a mass concentration of 60% were added and mixed evenly to prepare a positive electrode slurry, which was coated on the nickel foam through a slurry drawing mold, and after vacuum drying at 60°C for 12 hours, it was pressed at a pressure of 12MPa for 10 seconds to obtain a positive electrode plate.

[0069] Embodiment 11

[0070] Preparation of 2wt% Cr2O3 and 2wt% antimony doped tin oxide positive plate:

[0071] 0.38g of the composite positive electrode material prepared in Example 3, 0.01g of chromium oxide, 0.01g of antimony-doped tin oxide and 0.1g of superconducting carbon black were ground in an agate mortar for 20 minutes and mixed evenly. Then, 0.05g of a CMC solution with a mass concentration of 2.5% and 0.05g of a PTFE aqueous solution with a mass concentration of 60% were added and mixed evenly to prepare a positive electrode slurry, which was coated on the nickel foam through a slurry drawing mold, and after vacuum drying at 60°C for 12 hours, it was pressed at a pressure of 12MPa for 10 seconds to prepare a positive electrode plate.

[0072] Example 12

[0073] Preparation of 5wt% YbO doped positive plate:

[0074] 0.375 g of the composite positive electrode material prepared in Example 4, 0.025 g of ytterbium oxide and 0.1 g of superconducting carbon black were ground in an agate mortar for 20 min and mixed evenly. Then 0.05 g of a CMC solution with a mass concentration of 2.5% and 0.05 g of a PTFE aqueous solution with a mass concentration of 60% were added and mixed evenly to prepare a positive electrode slurry, which was coated on the nickel foam through a slurry drawing mold, and after vacuum drying at 60° C. for 12 h, it was pressed for 10 s at a pressure of 12 MPa to prepare a positive electrode plate.

[0075] Example 1-12 Battery assembly: The prepared positive electrode plate and the conventional zinc negative electrode plate are sandwiched with a zinc-nickel battery-specific separator, placed in a special simulated battery shell, and injected with electrolyte (a 6 mol / L KOH solution saturated with zinc oxide and containing 0.2% sodium hexafluoroantimonate) to assemble into a semi-sealed zinc-manganese secondary battery.

[0076] Comparative Example 1

[0077] Commercial manganese dioxide is used as the active material. Preparation of positive plate: 0.4g of manganese dioxide and 0.1g of superconducting carbon black are ground in an agate mortar for 20 minutes and mixed evenly. Then 0.05g of CMC solution with a mass concentration of 2.5% and 0.05g of PTFE aqueous solution with a mass concentration of 60% are added and mixed evenly to form a positive electrode slurry, which is coated on the nickel foam through a slurry drawing mold. After vacuum drying at 60°C for 12h, the positive plate is pressed at a pressure of 12MPa for 10s. The prepared positive plate and the conventional zinc negative plate are sandwiched between a special separator for zinc-nickel batteries, loaded into a special simulated battery shell, and the electrolyte (6mol / L KOH solution saturated with zinc oxide) is injected to assemble into a semi-sealed zinc-manganese secondary battery.

[0078] Battery performance test: The zinc-manganese secondary batteries prepared by using specific examples 1-12 and comparative example 1 were activated at 0.2C and then tested for capacity performance and cycle stability. After 0.2C charging, the battery was left for 10 minutes, and then discharged at 0.2C to 1.0V, and cycled 150 times to measure the capacity performance of the positive electrode material. The electrical performance test results of the zinc-manganese secondary batteries are listed in Table 1.

[0079] Table 1 Battery charge and discharge performance test

[0080]

[0081] From the above test results in Table 1 and Figure 4 It can be seen that the composite positive electrode material prepared by the present invention has good cycle stability and a higher discharge voltage platform. The improvement in cycle stability is mainly attributed to the modification of the structural lattice of the MnO2 positive electrode material by the layered hydroxide material, especially the presence of a large number of beneficial metal elements and the nano-layered structural morphology, which greatly reduces the deformation of the positive electrode during the reaction and inhibits the production of inert irreversible substances, thereby improving the reversible charge and discharge performance of the positive electrode during the charge and discharge process. Doping with different excellent positive electrode additives and improving the properties of the MnO2 electrode can improve the cycle stability of the positive electrode. At the same time, the selection of an effective electrolyte additive, sodium hexafluoroantimonate, can improve the overall electrical properties of the battery, which is beneficial to the improvement of the battery discharge platform and capacity.

[0082] Embodiment 13

[0083] MnO2 / layered hydroxide [Ni 0.8 Ti 0.2 (OH)2·[(A a- ) n ·mH2O](A=NO3 - , n=0.1, m=2) Preparation of composite positive electrode materials:

[0084] First, nickel nitrate and titanium sulfate are mixed at a molar ratio of Ni / Ti=0.8 / 0.2 and prepared at 25°C to prepare a composite salt solution with a molar concentration of 0.5 mol / L; potassium hydroxide is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 3 mol / L; the alkaline solution is added dropwise to the mixed salt solution at 25°C using a peristaltic pump, and stirred continuously until the pH of the reaction suspension reaches 9. After the reaction is completed, the obtained suspension is reacted at 80°C for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to a sodium nitrate solution with a molar concentration of 0.5 mol / L, treated at 130°C for 1 hour under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide. Then the electrolytic manganese dioxide precursor and the prepared layered hydroxide are mixed at a mass ratio of 3:1 and subjected to high-energy ball milling to obtain MnO2 / layered hydroxide [Ni 0.8 Ti 0.2 (OH)2·[(A a- ) n ·mH2O] composite positive electrode material.

[0085] Embodiment 14

[0086] MnO2 / layered hydroxide [Ni 0.75 Ti 0.15 Zn 0.1 (OH)2·[(A a- ) n ·mH2O](A= SO4 2- OH - , n=0.1, m=2) Preparation of composite positive electrode materials:

[0087] First, nickel sulfate, titanium sulfate and zinc sulfate are mixed in a molar ratio of Ni / Ti / Cu=0.7 / 0.2 / 0.1 and prepared into a composite salt solution with a molar concentration of 0.4 mol / L at room temperature; sodium hydroxide is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2 mol / L; at room temperature, the alkaline solution is added dropwise to the mixed salt solution, and stirred continuously until the pH of the reaction suspension reaches 9. After the reaction is completed, the obtained suspension is reacted at 90°C for 10 hours, cooled to room temperature, filtered, washed and dried to obtain a layered hydroxide. Manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor. The manganese dioxide precursor and the prepared layered hydroxide are mixed in a mass ratio of 2:1 and then subjected to high-energy ball milling to obtain a manganese dioxide composite nickel-titanium multi-layered hydroxide composite positive electrode material.

[0088] Embodiment 15

[0089] MnO2 / layered hydroxide [Ni 0.7 Ti 0.1 Co0.1 Y 0.1 (OH)2·[(A a- ) n ·mH2O](A=WO4 2- OH - , n=0.1, m=2) Preparation of composite positive electrode materials:

[0090] First, nickel sulfate, titanium sulfate, cobalt sulfate and yttrium nitrate are mixed in a molar ratio of Ni / Ti / Co / Y=0.7 / 0.15 / 0.1 / 0.05 and prepared into a composite salt solution with a molar concentration of 1.6 mol / L at room temperature; sodium hydroxide is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2.5 mol / L; at room temperature, the alkaline solution is added dropwise to the mixed salt solution, and stirred continuously until the pH of the reaction suspension reaches 8. After the reaction is completed, the obtained suspension is reacted at 60°C for 18h, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to an alkaline solution of sodium tungstate with a molar concentration of 2 mol / L, treated at 120°C for 4h under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide. The manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor. The manganese dioxide precursor and the prepared layered hydroxide are mixed in a mass ratio of 1:1 and then subjected to high-energy ball milling to obtain a MnO2 / layered hydroxide composite positive electrode material.

[0091] Example 16

[0092] MnO2 / partially oxidized layered hydroxide [Ni 0.8 Ti 0.1 Ca 0.1 (OH)2·[(A a- ) n ·mH2O](A=F - 、MoO4 3- , n=0.2, m=2) Preparation of composite positive electrode materials:

[0093] First, nickel acetate, titanium sulfate and calcium chloride are mixed in a molar ratio of Ni / Ti / Ca=0.8 / 0.1 / 0.1 and prepared at room temperature to form a composite salt solution with a molar concentration of 2.0 mol / L; potassium hydroxide is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2 mol / L; at room temperature, the alkaline solution is added dropwise to the mixed salt solution, and the reaction suspension is continuously stirred until the pH value of the reaction suspension reaches 9. After the reaction is completed, the obtained suspension is reacted at 80°C for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to a mixed solution of sodium fluoride and sodium molybdate with a molar concentration of 3.0 mol / L (the molar ratio of sodium fluoride to sodium molybdate is 2:1), treated at 150°C for 12 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide. Then, under nitrogen protection, 5 g of the layered hydroxide was added into 100 mL of 5 g of potassium persulfate and 1.0 M potassium hydroxide solution, stirred for 30 min, filtered, washed, and dried under vacuum at 80° C. for 5 h to obtain a partially oxidized layered hydroxide.

[0094] The manganese dioxide is ball-milled and sieved to obtain a manganese dioxide precursor. The manganese dioxide precursor and the prepared partially oxidized layered hydroxide are mixed in a mass ratio of 5:3 and then subjected to high-energy ball milling to obtain a MnO2 / partially oxidized layered hydroxide composite positive electrode material.

[0095] Embodiment 17

[0096] MnO2 / Layered oxyhydroxide[Ni 0.8 Ti 0.1 Al 0.1 OOH·[(A a- ) n ·mH2O]( A=PO4 3- , n=0.2, m=2) / Preparation of carbon nanotube composite positive electrode materials:

[0097] First, nickel nitrate, titanium sulfate and aluminum chloride are mixed in a molar ratio of Ni / Ti / Al=0.8 / 0.1 / 0.1 and prepared at 25°C to prepare a composite salt solution with a molar concentration of 0.5 mol / L, and then carbon nanotubes are ultrasonically dispersed in the composite salt solution, and the mass percentage of carbon nanotubes is about 2.5%; potassium hydroxide solid is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 3 mol / L; the alkaline solution is added dropwise to the mixed salt solution at 25°C by a peristaltic pump, and is continuously stirred until the pH of the inverse suspension reaches 8. After the reaction is completed, the obtained suspension is reacted at 80°C for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain powder; the obtained powder is transferred to a sodium phosphate solution with a molar concentration of 0.5 mol / L, treated at 150°C for 12 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide / carbon nanotube composite material. Then, under nitrogen protection, 5g of the layered hydroxide / carbon nanotube composite material was added to 100mL of 15g of potassium persulfate and 3M potassium hydroxide solution, stirred for 70min, filtered, washed, and vacuum dried at 60°C for 8h to obtain a layered oxyhydroxide / carbon nanotube composite material. Finally, electrolytic manganese dioxide and the layered oxyhydroxide / carbon nanotube composite material were mixed at a mass ratio of 3:2 and ball milled to obtain a MnO2 / layered oxyhydroxide / carbon nanotube composite material composite cathode material.

[0098] Embodiment 18

[0099] MnO2 / Layered oxyhydroxide[Ni 0.6 Ti 0.15 Sb 0.1 Ce 0.1 Bi 0.05 OOH·[(A a- ) n ·mH2O] (A=Cl - , n=0.2, m=2) / Preparation of titanium nitride composite positive electrode material:

[0100] First, nickel chloride, titanium sulfate, antimony chloride, cerium nitrate and bismuth nitrate are mixed in a molar ratio of Ni / Ti / Sb / Ce / Bi=0.6 / 0.15 / 0.1 / 0.1 / 0.05 and prepared at room temperature to prepare a composite salt solution with a molar concentration of 1.8 mol / L; potassium hydroxide solid is dissolved in deionized water to prepare an alkaline solution with a molar concentration of 2.5 mol / L; the alkaline solution is added dropwise to the mixed salt solution at 25°C by a peristaltic pump, and is continuously stirred until the pH of the reaction suspension reaches 8.5. After the reaction is completed, the obtained suspension is reacted at 80°C for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain a powder; the obtained powder is transferred to a sodium chloride solution with a molar concentration of 1.0 mol / L, treated at 120°C for 3 hours under the protection of inert gas nitrogen, filtered, washed, and dried to obtain a layered hydroxide. Then, under nitrogen protection, 5g of layered hydroxide was added to 100mL of 15g potassium persulfate and 3M potassium hydroxide solution, stirred for 70min, filtered, washed, and vacuum dried at 60°C for 8h to obtain layered oxyhydroxide. The electrolytic manganese dioxide solid powder was ground and sieved to obtain a manganese dioxide precursor for standby use. The manganese dioxide precursor, titanium nitride, and the prepared layered oxyhydroxide were ultrasonically dispersed in an aqueous solution at a mass ratio of 5:1:4, stirred at 50°C for 2h, and freeze-dried to obtain a MnO2 / layered oxyhydroxide / graphene composite positive electrode material.

[0101] Embodiment 19

[0102] Preparation of 1wt% Sr(OH)2-doped and 2wt% Sb-doped SnO positive plates:

[0103] 0.385g of the composite positive electrode material prepared in Example 15, 0.005g of strontium hydroxide, 0.01g of antimony-doped tin oxide and 0.1g of superconducting carbon black were ground in an agate mortar for 20 minutes and mixed evenly. Then, 0.05g of a CMC solution with a mass concentration of 2.5% and 0.05g of a PTFE aqueous solution with a mass concentration of 60% were added and mixed evenly to prepare a positive electrode slurry, which was coated on the nickel foam through a slurry drawing mold, and after vacuum drying at 60°C for 12 hours, it was pressed at a pressure of 12MPa for 10 seconds to obtain a positive electrode plate.

[0104] Example 13-19 Battery assembly: The prepared positive electrode plate and the conventional zinc negative electrode plate are sandwiched with a special separator for zinc-manganese batteries, placed in a special simulated battery shell, and injected with electrolyte (6 mol / L KOH solution saturated with zinc oxide and containing 0.2 wt% sodium hexafluoroantimonate) to assemble into a semi-sealed zinc-manganese secondary battery.

[0105] Comparative Example 2

[0106] Commercial manganese dioxide was used as the active material.

[0107] Commercial manganese dioxide is used as the active material. Preparation of positive plate: 0.39g of manganese dioxide, 0.01g of bismuth oxide, and 0.1g of superconducting carbon black are ground in an agate mortar for 20 minutes and mixed evenly. Then 0.05g of CMC solution with a mass concentration of 2.5% and 0.05g of PTFE aqueous solution with a mass concentration of 60% are added and mixed evenly to form a positive electrode slurry, which is coated on the nickel foam through a slurry drawing mold. After vacuum drying at 60°C for 12h, the positive plate is pressed at a pressure of 12MPa for 10s. The prepared positive plate and the conventional zinc negative plate are sandwiched between a special diaphragm for zinc-manganese batteries, loaded into a special simulated battery shell, and the electrolyte (6mol / L KOH solution saturated with zinc oxide) is injected to assemble into a semi-sealed zinc-manganese secondary battery.

[0108] Battery performance test: The batteries made by using specific examples 13-21 and comparative example 2 were activated at 0.2C and then tested for capacity performance and cycle stability. After 0.2C charging, the battery was left for 10 minutes, then discharged at 0.2C to 1.0V, and cycled 150 times to measure the capacity performance of the positive electrode material. The battery electrical performance test results are listed in Table 2.

[0109] Table 2 Battery charge and discharge performance test

[0110]

[0111] From the above test results in Table 2 and Figure 7 It can be seen that the composite positive electrode material prepared by the present invention has good cycle stability and a higher discharge voltage platform. The improvement in cycle stability is mainly attributed to the modification of the structural lattice of the MnO2 positive electrode material by layered hydroxide, especially the presence of a large number of beneficial metal elements and the nano-layered structural morphology, which greatly reduces the deformation of the positive electrode during the reaction and inhibits the production of inert irreversible substances, thereby improving the reversible charge and discharge performance of the positive electrode during the charge and discharge process. Doping with different excellent additives and improving the properties of the MnO2 electrode can improve the cycle stability of the positive electrode. At the same time, the selection of an effective electrolyte additive, sodium hexafluoroantimonate, can improve the overall electrical performance of the battery, which is beneficial to the improvement of the battery discharge platform and capacity.

[0112] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A low-cost alkaline secondary battery positive electrode material, characterized in that: The positive electrode material is composed of manganese dioxide and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] composite cathode material, or manganese dioxide and partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] composite cathode material, or manganese dioxide and layered oxyhydroxide [Ni x M y A Z OOH] composite positive electrode material, or manganese dioxide, conductive material and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or layered oxyhydroxide [Ni x M y A Z OOH] to form a composite positive electrode material, the composite positive electrode material has a three-dimensional structure, a multi-level pore structure or a coating structure, or a mixed structure of multiple structures, wherein M is Bi or Ti, A is one or two of Ce, Al, Zn, Ca, Mg, Co, Y, Ga, Sb, Yb or Cu, and B a- OH − , Cl - 、F - PO4 3- 、SO4 2- 、CO3 2− 、NO3 − , BO2 - 、MoO4 2- or WO4 2- One or more of, 0.9≥x≥0.5, 0.3≥y≥0.1, 0.2≥z≥0.01, x+y+z=1, b>0, m>0.

2. The low-cost alkaline secondary battery positive electrode material according to claim 1, characterized in that: The layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or layered oxyhydroxide [Ni x M y A Z The mass percentage of OOH] is 5%-75%.

3. The low-cost alkaline secondary battery positive electrode material according to claim 1, characterized in that: The conductive material is one or two of graphene, carbon nanotubes, acetylene black, flake graphite, cobalt oxyhydroxide, nitrogen carbide, titanium carbide, niobium carbide or titanium nitride, and the mass percentage of the conductive material in the composite positive electrode material is 0.5%-20%; the manganese dioxide is one or more of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2 or ε-MnO2.

4. A method for preparing a low-cost alkaline secondary battery positive electrode material according to claim 1, characterized in that The manganese dioxide and layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b The specific preparation process of the composite positive electrode material composed of ·mH2O] is as follows: Step S1, ball-milling a manganese dioxide precursor, and sieving to obtain a manganese dioxide precursor for standby use; Step S2, dissolving a soluble nickel salt, a soluble bismuth salt or a soluble titanium salt, and a metal salt of A in deionized water to prepare a composite salt solution, dissolving an alkaline hydroxide in deionized water to prepare an alkaline solution, adding the alkaline solution to the composite salt solution at 15-50° C., and continuously stirring until the pH of the suspension reaches 7-11 after the reaction is completed, reacting the obtained suspension at 50-95° C. for 5-48 hours, cooling to room temperature, filtering, washing, and drying to obtain a powder, transferring the obtained powder to a solution prepared by one or more of an alkaline hydroxide, a phosphate, a tungstate, a molybdate, a chloride, a fluoride, a carbonate, a metaborate, or a borate, treating at 25-200° C. for 1-24 hours under an inert atmosphere or air conditions, filtering, washing, and drying to obtain a layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O]; Step S3, mixing the manganese dioxide precursor obtained in step S1 and the layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] and then subjected to high-energy ball milling to obtain a composite positive electrode material.

5. A method for preparing a low-cost alkaline secondary battery positive electrode material according to claim 1, characterized in that The manganese dioxide and the partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] composite positive electrode material and manganese dioxide and layered oxyhydroxide [Ni x M y A Z The specific preparation process of the composite positive electrode material composed of OOH is as follows: Step S1, ball-milling a manganese dioxide precursor, and sieving to obtain a manganese dioxide precursor for standby use; Step S2, dissolving a soluble nickel salt, a soluble bismuth salt or a soluble titanium salt, and a metal salt of A in deionized water to prepare a composite salt solution, dissolving an alkaline hydroxide in deionized water to prepare an alkaline solution, adding the alkaline solution to the composite salt solution at 15-50° C., and continuously stirring until the pH of the suspension reaches 7-11 after the reaction is completed, reacting the obtained suspension at 50-95° C. for 5-48 hours, cooling to room temperature, filtering, washing, and drying to obtain a powder, transferring the obtained powder to a solution prepared by one or more of an alkaline hydroxide, a phosphate, a tungstate, a molybdate, a chloride, a fluoride, a carbonate, a metaborate, or a borate, treating the solution at 25-200° C. for 1-24 hours under an inert atmosphere or air, filtering, washing, and drying to obtain a layered hydroxide, and oxidizing the layered hydroxide by a chemical oxidation or electrolytic oxidation method to obtain a partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH]; Step S3, the manganese dioxide precursor obtained in step S1 and the partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH] and then subjected to high-energy ball milling to obtain a composite positive electrode material.

6. A method for preparing a low-cost alkaline secondary battery positive electrode material according to claim 1, characterized in that The manganese dioxide, the conductive material and the layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or layered oxyhydroxide [Ni x M y A Z The specific preparation process of the composite positive electrode material composed of OOH is as follows: Step S1, ball-milling a manganese dioxide precursor, and sieving to obtain a manganese dioxide precursor for standby use; Step S2, dissolving a soluble nickel salt, a soluble bismuth salt or a soluble titanium salt, and a metal salt of A in deionized water to prepare a composite salt solution, dissolving an alkaline hydroxide in deionized water to prepare an alkaline solution, adding the alkaline solution to the composite salt solution at 15-50° C., and continuously stirring until the pH of the suspension reaches 7-11 after the reaction is completed, reacting the obtained suspension at 50-95° C. for 5-48 hours, cooling to room temperature, filtering, washing, and drying to obtain a powder, transferring the obtained powder to a solution prepared by one or more of an alkaline hydroxide, a phosphate, a tungstate, a molybdate, a chloride, a fluoride, a carbonate, a metaborate, or a borate, treating at 25-200° C. for 1-24 hours under an inert atmosphere or air conditions, filtering, washing, and drying to obtain a layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O], the layered hydroxide is oxidized by chemical oxidation or electrolytic oxidation to obtain a partially oxidized layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH]; Step S3, mixing the manganese dioxide precursor obtained in step S1, the conductive material and the layered hydroxide [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or partially oxidized layered hydroxides [Ni x M y A Z (OH)2]·[(B a- ) b ·mH2O] or fully oxidized layered oxyhydroxides [Ni x M y A Z OOH] is uniformly dispersed in water or an organic solvent, reacted in a normal pressure container at 15-90° C., and then the product is dried to obtain a composite positive electrode material.

7. The method for preparing a low-cost alkaline secondary battery positive electrode material according to any one of claims 4 to 6, characterized in that: The soluble nickel salt is one or more of nickel nitrate, nickel sulfate, nickel acetate or nickel chloride; the soluble bismuth salt is bismuth nitrate; the soluble titanium salt is titanium sulfate; the A metal salt is one or more of cerium nitrate, cerium chloride, aluminum nitrate, aluminum chloride, aluminum sulfate, zinc nitrate, zinc sulfate, zinc chloride, calcium acetate, calcium chloride, magnesium acetate, magnesium chloride, cobalt nitrate, cobalt chloride, cobalt sulfate, yttrium nitrate, yttrium sulfate, yttrium chloride, gallium nitrate, antimony sulfate, antimony chloride, ytterbium nitrate, ytterbium chloride, copper chloride, copper sulfate or copper nitrate; the phosphate is one or more of potassium phosphate, sodium hydrogen phosphate or sodium phosphate ; The tungstate is one or more of potassium tungstate, sodium tungstate or lithium tungstate; the molybdate is one or more of potassium molybdate or sodium molybdate; the chloride is one or more of potassium chloride or sodium chloride; the fluoride is one or more of potassium fluoride or sodium fluoride; the carbonate is one or more of potassium carbonate or sodium carbonate; the metaborate is one or more of potassium metaborate, sodium metaborate or lithium metaborate; the borate is one or more of potassium metaborate, sodium metaborate or lithium metaborate; the alkaline hydroxide is one or more of sodium hydroxide, potassium hydroxide or lithium hydroxide.

8. An alkaline secondary battery positive plate, characterized in that: The alkaline secondary battery positive electrode plate is made from the low-cost alkaline secondary battery positive electrode material according to any one of claims 1 to 3.

9. The alkaline secondary battery positive plate according to claim 8, characterized in that: The low-cost alkaline secondary battery positive electrode material is added with an additive with a mass fraction of 0.5% to 10%, and the additive is one or two of chromium oxide, chromium hydroxide, strontium oxide, strontium hydroxide, ytterbium oxide or antimony-doped tin oxide.

10. An alkaline secondary battery, comprising a battery housing, a plate group sealed in the battery housing, and an electrolyte, wherein the plate group comprises a positive plate, a negative plate, and a separator, characterized in that: The positive electrode plate is the alkaline secondary battery positive electrode plate of claim 8, and the electrolyte is a potassium hydroxide alkaline solution, and sodium hexafluoroantimonate is added at a mass fraction of 0.1% to 2%.

Citation Information

Patent Citations

  • Long-cycle and high-safety power lithium ion battery positive electrode material and preparation method thereof

    CN105406056A

  • Zinc-nickel battery anode material and its preparation method and battery using anode material

    CN106848315A